Realism and ritual in the rhetoric of fiction: anti-theatricality and anti-catholicism in Brontë, Newman and Dickens - Fanucchi, Sonia (My University, 2016)
This thesis is concerned with the meeting point between theatre and religion in the mid-Victorian consciousness, and the paradoxical responses that this engendered particularly in the novels and thought of Dickens, Newman and Charlotte Brontë. It contributes to the still growing body of critical literature that attempts to tease out the complex religious influences on Dickens and Brontë and how this manifests in their fiction. Newman is a religious writer whose fictional treatment of spiritual questions in Callista (1859) is used as a foil to the two novelists. There are two dimensions to this study: on the one hand it is concerned with the broader cultural anti-Catholic mood of the period under consideration and the various ways in which this connects with anti-theatricality. I argue that in the search for a legitimate means of expressing religious sentiments, writers react paradoxically to the latent possibilities of the conventions of religious ceremony, which is felt to be artificial, mystical, transcendent and threatening, inspiring the same contradictory responses as the theatre itself. The second dimension of this study is concerned with the way in which these sentiments manifest themselves stylistically in the novels under consideration: through a close reading of Barnaby Rudge (1841), Pictures From Italy (1846), and Villette (1852), I argue that in the interstices of a wariness of Catholicism and theatricality there is a heightening of language, which takes on a ritual dimension, evoking the paradoxical suggestions of transcendent meaning and artificiality associated with performance. Newman’s Callista (1859) acts as a counterpoint to these novels, enacting a more direct and persuasive argument for the spiritual value of ritual. This throws some light on the realist impulse in the fiction of Brontë and Dickens, which can be thought of as a struggle between a language that seeks to distance and explain, and a language that seeks to perform, involve, and inspire. In my discussion of Barnaby Rudge (1841) I argue that the ritual patterns in the narrative, still hauntingly reminiscent of a religious past, never become fully embodied. This is because the novel is written in a style that could be dubbed “melodramatic” because it both gestures towards transcendent presences and patterns and threatens to make nonsense of the spiritual echoes that it invokes. This sense of a gesture deferred is also present in the travelogue, Pictures from Italy (1846). Here I argue that Dickens struggles to maintain an objective journalistic voice in relation to a sacramental culture that is defined by an intrusive theatricality: he experiences Catholic practices and symbolism as simultaneously vital, chaotic and elusive, impossible to define or to dismiss. In Villette (1852) I suggest that Charlotte Brontë presents a disjuncture between Lucy’s ardour and the commonplace bourgeoisie world that she inhabits. This has the paradoxical effect of revitalising the images of the Catholic religion, which, despite Lucy’s antipathy, achieves a ghostly presence in the novel. In Callista (1859), I suggest that Newman concerns himself with the ritual possibilities and limitations of fiction, poetry and theatre. These dramatic and literary categories invoke and are ultimately subsumed in Christian ritual, which Newman considers the most refined form of language – the point at which detached description gives way to communion and participation. Keywords: Victorian literature, Charles Dickens, Charlotte Brontë, John Henry Newman, ritual, religion, realism, theatricality, anti-Catholicism
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of Doctor of Philosophy, Johannesburg, 2016.
Keywords: Newman, John Henry,--1801-1890--Religion; Dickens, Charles,--1812-1870--Religion; Brontë, Charlotte,--1816-1855--Religion; English literature--19th century--History and criticism; Religion and literature--History--19th century; Christianity and literature--History--19th century; Realism in literature